Domain Wall Motions in a Near-Morphotropic Pb(Zr,Ti)O3 Under Mechanical Stress Observed by In Situ Piezoresponse Force Microscopy - Kim, Kwanlae (Korean Journal of Metals and Materials, 2019)
Many important material properties of ferroelectric ceramics such as piezoelectric coefficient and hysteresis curve are governed by domain structures and their evolution processes. In the present work, domain wall motions in a near-morphotropic Pb(Zr,Ti)O3 under an external compressive stress were observed using in situ piezoresponse force microscopy (PFM). This specific PZT material was chosen due to its complex microstructure, which originates from the coexistence of tetragonal and rhombohedral phases. A micromechanical test rig was installed on the sample stage controller, enabling precise control of the sample position. For the real-time strain monitoring of the PZT sample, a strain gauge was attached to the sample surface on which the PFM scan was conducted. In addition, analysis of the ferroelectric domain structure was assisted by using the electron backscatter diffraction (EBSD) technique to identify the habit planes of non- 180° domain walls and grain boundaries in the PFM images. From a certain grain, a set of large non-180° needle-like domain patterns in the (101) plane were observed before applying a mechanical stress. With increasing compressive stress levels, another set of non-180° needle-like domain patterns grew in the (011) plane, overwriting the domain patterns in the (101) plane. This indicates that polarization switching processes in ferroelectric ceramics take place via a pattern evolution based on the pre-existing domain patterns. KCI Citation Count: 2